COVID-19: how has a global pandemic changed manual therapy technique education in chiropractic programs around the world? - Katie de Luca; Marcus McDonald; Laura Montgomery; Stephen Sharp; Anika Young; Simon Vella; Michelle M. Holmes; Sasha Aspinall; Danica Brousseau; Chris Burrell; David Byfield; Dawn Dane; et al. (Chiropractic & Manual Therapies, 2021)
Abstract Background Manual therapy is a cornerstone of chiropractic education, whereby students work towards a level of skill and expertise that is regarded as competent to work within the field of chiropractic. Due to the COVID-19 pandemic, chiropractic programs in every region around the world had to make rapid changes to the delivery of manual therapy technique education, however what those changes looked like was unknown. Aims The aims of this study were to describe the immediate actions made by chiropractic programs to deliver education for manual therapy techniques and to summarise the experience of academics who teach manual therapy techniques during the initial outbreak of COVID-19 pandemic. Methods A qualitative descriptive approach was used to describe the immediate actions made by chiropractic programs to deliver manual therapy technique education during the COVID-19 pandemic. Chiropractic programs were identified from the webpages of the Councils on Chiropractic Education International and the Council on Chiropractic Education – USA. Between May and June 2020, a convenience sample of academics who lead or teach in manual therapy technique in those programs were invited via email to participate in an online survey with open-ended questions. Responses were entered into the NVivo software program and analysed using a reflexive thematic analysis by a qualitative researcher independent to the data collection. Results Data from 16 academics in 13 separate chiropractic programs revealed five, interconnected themes: Immediate response; Move to online delivery; Impact on learning and teaching; Additional challenges faced by educators; and Ongoing challenges post lockdown. Conclusion This study used a qualitative descriptive approach to describe how some chiropractic programs immediately responded to the initial outbreak of the COVID-19 pandemic in their teaching of manual therapy techniques. Chiropractic programs around the world provided their students with rapid, innovative learning strategies, in an attempt to maintain high standards of chiropractic education; however, challenges included maintaining student engagement in an online teaching environment, psychomotor skills acquisition and staff workload.